Застосування комплексної методології для оптимізації проточних частин парових турбін - Авдєєва, Олена Петрівна; Усатий, Олександр Павлович; Пальков, Ігор Андрійович; Пальков, Сергій Андрійович (Національний технічний університет "Харківський політехнічний інститут", 2020)
В статті викладено ефективність застосування комплексної методології при модернізації існуючих проточних частин парових турбін. Наведена методологія дозволяє збільшити абсолютний ККД на 0,83 %, а потужність турбіни на 1,87 % за рахунок використання об’єктно-орієнтованого підходу. Використання рекурсивного обходу різних рівнів оптимізації задля обміну інформацією між об’єктами дозволяє знайти оптимальне рішення для великої кількості конструктивних параметрів.

The article describes the effectiveness of the application of a comprehensive methodology in the modernization of the flow paths of steam turbines. The paper considers two approaches to optimizing the flow path of steam turbines. The first approach is based on the independent optimization of individual turbine objects: nozzle steam distribution system, high, medium and low pressure cylinders. The second approach was to comprehensively optimize the entire flow path of steam turbines. The studies have shown the advantages of applying the second approach to the optimization of powerful steam turbines, which consist in increasing the efficiency of the turbine by taking into account the mutual influence of the turbine objects during complex optimization. The above methodology makes it possible to increase the absolute efficiency by 0.83 %, and the turbine power by 1.87 % due to the use of an object-oriented approach. The use of recursive traversal of various optimization levels for information exchange between objects allows finding an optimal solution for a large number of design parameters.
Application of a comprehensive methodology to optimize the flow paths of steam turbines
Keywords: ефективність; efficiency